Feedstocks, Methods and Perspectives of Biodiesel Production - Anna Yu. Kuchkina; Nadezhda N. Sushchik (Журнал Сибирского федерального университета: Серия Биология, 2014)
Backgrounds, stages of development and contemporary achievements of bioenergetics are considered in the review. We focus on production of biodiesel which is renewable, ecological safety fuel for transport and an alternative for petrodiesel. Main feedstocks, technological stages of biodiesel production and their effect on fuel properties were concerned. Economical, ecological and energetic problems related with biodiesel production from various bioresources were analysed. As shown, at present the most part of biodiesel in the world is produced from agricultural crop oils. High cost and negative ecological and economical consequences of use of agricultural crops as the feedstock resulted in development of production of “advanced” biofuel, i.e., that based on biomass of microorganisms and various biowastes. However, growth and treatment of microalgae biomass for biodiesel production are still costly and unsustainable. Different ways for improving of such biodiesel cost are supposed, e.g. integrated microbial processes for biofuel and high value-added products or simultaneous wastewater treatment. Production of biodiesel from feedstocks which are various biowastes (for instance, municipal sewage sludges, or bottom sediments dredged from recovered eutrophic water bodies) appeared to be the most economically profitable since such feedstock is cost-free and an important ecological issue of utilization of such wastes is resolved